A Negative Life Event Impairs Psychosocial Stress, Recovery and Running Economy of Runners - Otter, R. T. A.; Brink, M. S.; Diercks, R. L.; Lemmink, K. A. P. M. (International Journal of Sports Medicine, 2016)
The purpose was to investigate how a negative life event (NLE) affects perceived psychosocial stress, recovery and running economy (RE). Competitive runners were monitored in a prospective non-experimental cohort study over one full training season in which they experienced the same unplanned severe NLE. 16 runners recorded stress and recovery scores (RESTQ-Sport) every week. The average scores over 3 weeks before the NLE were used as a baseline and were compared to scores during the week of the NLE (week 0), week 1 and week 2. 7 runners completed a submaximal treadmill test before and after the NLE. Repeated measures ANOVAs revealed that most scores on general stress scales were increased in week 0 and 1. Of the general recovery scales, “general well-being” was decreased in week 0 and 1, “social” and “physical recovery” were decreased in week 0. No changes in the sport-specific stress scales were found. However, 2 of the sport-specific recovery scales were decreased in week 0. An impaired RE was shown 3 weeks after the NLE. Therefore, it is important to know what is going on in an athlete’s life, because stressful life events alter RE after the stress and recovery already returned to normal levels.
Keywords: perceived stress; competitive athletes; athletic training; exercise test; major life event